Permeable resin capable of realizing X-ray development, preparation method and application of permeable resin in preparation of material for diagnosing and treating subfissure teeth

By developing an X-ray developing permeable resin, which combines X-ray development, fluidity and bonding and sealing functions, solves the problems of diagnosis and treatment of cryptoclase teeth, and realizes effective minimally invasive diagnosis and treatment of cryptoclase teeth.

CN119679974APending Publication Date: 2025-03-25NANJING STOMATOLOGICAL HOSPITAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411847794.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art lacks effective minimally invasive diagnostics and treatments for cryptoclase teeth, especially when cracks in the root cause bacteria to enter periodontal tissue, resulting in the teeth eventually having to be removed.

Method used

An X-ray developing permeable resin is developed, which is a network-like polymer formed by polymerizing a resin matrix and a developer by a crosslinking agent, and has X-ray development, fluidity and bonding and sealing functions for diagnosing and treating cryptoclase teeth.

Benefits of technology

This material can help diagnose the crack distribution of cryptoclase teeth through X-ray development, and delay the progress of cracks through the bonding and sealing function, achieving minimally invasive treatment of cryptoclase teeth and avoid tooth extraction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189716910000021
    Figure BDA0005189716910000021
  • Figure HDA0005189716920000011
    Figure HDA0005189716920000011
  • Figure HDA0005189716920000021
    Figure HDA0005189716920000021
Patent Text Reader

Abstract

The invention discloses X-ray developing permeable resin, a preparation method and application in preparation of a material for diagnosing and treating subfissure teeth, and belongs to the technical field of dental diagnosis and treatment. The X-ray developing permeable resin is a network-shaped polymer formed by polymerizing a resin matrix and a developing agent through a cross-linking agent; the developing agent is an iodinated chemical substance containing unsaturated bonds. The X-ray developing permeable resin material provided by the invention has X-ray radiation resistance, can help to diagnose fine cracks, can permeate into the cracks while developing, seals the cracks and prevents the cracks from further expanding, so that the purpose of retaining diseased teeth in vivo is achieved, and diagnosis and treatment integration of hidden fissure teeth is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tooth diagnosis and treatment, and relates to a material for diagnosing and treating cracked teeth, and in particular to an X-ray-developable permeable resin and a preparation method thereof, and application in the preparation of materials for diagnosing and treating cracked teeth. Background Art

[0002] Tooth cracks, also known as incomplete tooth cracks or micro-cracks, are common non-caries diseases of the tooth. Cracked teeth have become the third leading cause of tooth loss after caries and periodontal disease. Since cracks in cracked teeth are small and hidden, early diagnosis of many cracked teeth is very difficult. On the other hand, for cracked teeth that have been clearly diagnosed, cracks that occur in the crown are usually treated with crown restorations or fillings due to the lack of effective bonding and sealing methods. However, when cracks occur in the root of the tooth, bacteria can enter the periodontal tissue through the cracks, which can cause extensive damage to the tissue, and the affected tooth can only be extracted in the end.

[0003] Infiltration resin is a minimally invasive resin infiltration system, which is a common material used in clinical practice for aesthetic restoration of early caries and post-orthodontic chalky spots before substantial defects. Low-viscosity infiltration resin can infiltrate into the porous structure of demineralized enamel through capillary siphoning, block the channels for acidic substance invasion and mineral dissolution and loss, form a barrier inside the lesion, and ultimately play a role in remineralization and treatment of early caries.

[0004] However, there is currently a lack of effective minimally invasive diagnosis and treatment methods for clinical cracked teeth; the existing infiltration resins used in the market, although they have good fluidity and sealing properties, are not radiopaque. Summary of the invention

[0005] The invention provides an X-ray-developable infiltration resin and a preparation method thereof, and application of the resin in preparing materials for diagnosing and treating cracked teeth, so as to overcome the defects of the prior art.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an X-ray-developable permeable resin, which is a network polymer formed by polymerization of a resin matrix and a developer through a crosslinking agent, and has the structure:

[0008]

[0009] The developer is an iodinated chemical substance containing an unsaturated bond.

[0010] Furthermore, the developer is one of (E)-3-iodoacrylate methyl, (E)-3-iodoacrylate ethyl, 3-iodo-2-propynyl N-butylcarbamate, iodo-2-ethyl acrylate, and 3-iodo-2-ethyl acrylate.

[0011] Furthermore, the resin matrix is ​​one of bisphenol A-glycidyl methacrylate (Bis-GMA), bisphenol-S-bis(3-methacryloyloxy-2-hydroxypropyl) ether (BisS-GMA), urethane dimethacrylate (UDMA), and isosorbide core-linked glycidyl methacrylate (Iso-GMA).

[0012] Furthermore, the cross-linking agent is one of triethylene glycol dimethacrylate (TEGDMA) and tricyclododecane dimethanol diacrylate (SR833s).

[0013] In a second aspect, the present invention also provides a method for preparing the above-mentioned X-ray-developable infiltration resin, comprising the following steps: step 1, mixing the resin matrix, cross-linking agent, photoinitiator and accelerator evenly under light-proof conditions to obtain an infiltration resin prepolymer; step 2, adding a developer to the infiltration resin prepolymer obtained in step 1, and continuing to mix evenly under light-proof conditions to obtain a developed infiltration resin prepolymer; step 3, when in use, light-curing the developed infiltration resin prepolymer obtained in step 2, and polymerizing to obtain the X-ray-developable infiltration resin.

[0014] Further, in step 1, the photoinitiator is one of camphorquinone (CQ), 1-phenyl-1,2-propanedione (Benzil), benzophenone (Benzophenone), 2-isopropylthioxanthone (ITX), and trimethylbenzoyl-diphenylphosphine oxide (TPO-L);

[0015] Furthermore, in step 1, the accelerator is ethyl 4-dimethylaminobenzoate (4E).

[0016] Furthermore, in step 1, the mass ratio of the resin matrix, the crosslinking agent, the photoinitiator and the accelerator is 27-50:31-70:0.5-1.5:0.5-3.45.

[0017] Furthermore, in step 2, the mass ratio of the developer to the infiltration resin prepolymer is 0.1 to 0.5:1.

[0018] Furthermore, in step 2, before the infiltration resin prepolymer and the developer are mixed, they are deoxygenated alternately by ultrasound and argon gas.

[0019] Furthermore, in step 3, the illumination time is 40 seconds.

[0020] In a third aspect, the present invention also provides the use of the above-mentioned X-ray-developable infiltration resin in the preparation of materials for diagnosing and treating cracked teeth. The X-ray-developable infiltration resin can perform X-ray development of the crack distribution and direction of cracked teeth, helping clinicians to make a clear diagnosis; at the same time, it can also bond and seal cracks, delay crack progression, and achieve minimally invasive treatment of cracked teeth.

[0021] The beneficial effects of the present invention are as follows: the present invention provides an X-ray developable infiltration resin, which has X-ray development, high fluidity and bonding and sealing functions, and can be used for the diagnosis and minimally invasive treatment of cracked teeth. Specifically, the X-ray developable infiltration resin is an iodine-containing infiltration resin, and the iodine substance contained therein has X-ray development ability, and can be used for the diagnosis of cracked teeth; at the same time, the reasonable ratio of the resin matrix and the cross-linking agent ensures the high fluidity, good permeability and certain bonding and sealing ability of the material, and can be used for the bonding and sealing of cracks in cracked teeth, delaying the progression of cracked teeth, and realizing minimally invasive treatment of cracked teeth. The material of the present invention effectively combines the developing component and the resin material, and its X-ray blocking performance helps diagnose small cracks, and while developing, the material penetrates into the cracks, sealing the cracks to prevent further expansion of the cracks, thereby achieving the purpose of retaining the affected teeth in the body, and realizing the integrated diagnosis and treatment of cracked teeth. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a Fourier infrared spectrum of the X-ray developable infiltration resin obtained in Example 1;

[0023] Figure 2 is a Fourier infrared spectrum of the X-ray developable infiltration resin obtained in Example 2;

[0024] Figure 3 It is the experimental data graph of the UV-visible light absorption test of the X-ray-developable penetrant resin;

[0025] Figure 4 It is the X-ray opacity result diagram of the X-ray-developable penetrant resin development effect test;

[0026] Figure 5 This is a diagram showing the sealing test results of the X-ray-displayable penetrant resin;

[0027] Figure 6 This is a graph showing the hardness test results of the X-ray-displayable penetrant resin;

[0028] Figure 7 This is a graph showing the adhesion test results of an X-ray-displayable penetrant resin. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments.

[0030] Example 1

[0031] The present embodiment provides an X-ray-developable infiltration resin for diagnosing and treating cracked teeth, and the preparation method thereof is as follows: take 210.6 mg Bis-GMA and 500 μl TEGDMA in an ep tube, shake on an oscillator at 3000 r / min for 5 minutes under light-proof conditions, add 3.9 mg CQ and 11.7 mg 4E, and continue to shake on the oscillator at 3000 r / min for 5 minutes. Place on the shaker for 1 hour to ensure that all components are fully dissolved and mixed to obtain an infiltration resin prepolymer. Weigh the total mass of the infiltration resin prepolymer, take 20% by mass of (E)-3-iodoacrylate methyl ester and add it to the ep tube, continue to shake for 5 minutes, and obtain a developing infiltration resin prepolymer. The obtained developing infiltration resin prepolymer is polymerized under light and then ground into powder, Figure 1 The Fourier infrared spectrum of the substance shows that the spectrum of the X-ray-developable infiltrated resin is 437.07 cm-1, compared with that without developer. -1 The emergence of a new peak at , proved that the substance was successfully synthesized.

[0032] Example 2

[0033] This embodiment provides an X-ray-developable infiltration resin for diagnosing and treating cracked teeth. The preparation method is basically the same as that of Example 1, except that the developer in Example 1 is replaced with (E)-3-iodoacrylate. The obtained product is measured by Fourier infrared spectroscopy. The results are as follows: Figure 2 As shown, the X-ray-developable infiltrated resin is 472.12 cm higher than that without developer. -1 The emergence of a new peak at , proved that the substance was successfully synthesized.

[0034] X-rayable infiltrated resin is used to diagnose and treat cracked teeth. The relevant performance tests and results are as follows:

[0035] 1. UV-visible light absorption test

[0036] (E)-3-iodoacrylate methyl ester was prepared into ethanol solutions with concentrations of 0.0025 mg / ml, 0.005 mg / ml, 0.008 mg / ml, and 0.01 mg / ml, and the absorbance was measured using a UV-visible spectrophotometer. The results are as follows: Figure 3 As shown in A.

[0037] Prepare the infiltration resin prepolymer according to Example 1, take 200 μl, weigh its mass to be 0.2186 g, take 20% mass fraction of (E)-3-iodoacrylate methyl ester and add it, at this time the concentration of the developer is 218.5 mg / ml, mix thoroughly and react for several hours, then light cure to form a cylinder, and immerse the cylinder in a certain volume of anhydrous ethanol for two days. The absorbance of (E)-3-iodoacrylate methyl ester in the leaching solution is measured by UV-visible spectrophotometer. Figure 3In B, the fitted (E)-3-iodoacrylate methyl standard concentration curve is used. The absorbance of (E)-3-iodoacrylate methyl in the measured leaching solution is substituted to obtain the concentration of (E)-3-iodoacrylate methyl in the leaching solution, and the reaction rate is finally calculated to be 98.31%.

[0038] 2. Development effect test

[0039] The X-ray-developable infiltration resin prepared in Example 1 was used to test the development effect. The collected teeth with occult longitudinal root fractures after root canal treatment were taken with cone beam CT as a blank control group, and the developing infiltration resin prepolymer and ICON were applied. The steps are as follows: take out the affected tooth and blow dry the surface with water-free and oil-free compressed air, apply 15% hydrochloric acid gel to the crack area, and etch for 2 minutes; blow it clean and wash it with water for 30 seconds, then blow it dry with a water-free and oil-free air gun; use anhydrous ethanol to thoroughly dehydrate and dry the lesion area at the crack, and blow it dry with a water-free and oil-free air gun after 30 seconds; apply the developing infiltration resin prepolymer or ICON to the crack area and act on it for 3 minutes; wipe with a cotton swab to remove excess material and then light cure for 40 seconds; apply the resin again, remove excess material again after 1 minute and perform light curing for 40 seconds. Take a CBCT again and compare the scanning grayscale values. The results are as follows Figure 4 As shown, the results showed that the X-ray developable infiltration resin group made the crack area more obvious, and the grayscale value of the X-ray developable infiltration resin group was much higher than that of the blank control group, indicating that the X-ray developable infiltration resin has a strong X-ray development effect.

[0040] 3. Closed testing

[0041] The ex vivo teeth that were photographed with CBCT in the development effect test were embedded with dental self-curing plastic and placed in a silicone rubber mold for shaping. After the self-curing plastic was left for 24 hours to release heat and harden, the roots with longitudinal cracks were cut perpendicular to the long axis of the tooth using a slow cutting machine to form a 2mm thick slice. After drying and gold spraying with an ion sputtering device, the resin penetration depth and crack sealing were observed using a scanning electron microscope. The results are as follows: Figure 5 The sealing rate of the developed penetrant resin group reached 100%, indicating good sealing performance.

[0042] 4. Hardness test

[0043] According to the preparation method of Example 1, an X-ray-developable penetrating resin was synthesized, wherein the mass fractions of (E)-3-iodoacrylate methyl ester were added in different mass fractions of 0, 10%, 20%, 30%, 40%, and 50%, respectively. Under light, it was prepared into a cylinder with a diameter and height of 10mm*10mm. The material was stored at room temperature of 23±2℃ for at least one hour before testing. The indenter was pressed into the sample with spring force, and then the indenter was pressed on the sample with contact force for 15s. The indentation depth of the sample was between 0 and 2.5mm, and the hardness value was obtained. Five measurements were performed for each group and the average value was taken. The results are as follows Figure 6 As shown, the results show that each component has a certain hardness, and as the mass fraction of the added developer increases, the hardness value tends to decrease.

[0044] 5. Adhesion test

[0045] The collected teeth with hidden longitudinal root fractures after root canal treatment stored in 4°C normal saline were removed; a slow cutting machine was used to remove the crown enamel in a direction perpendicular to the long axis of the tooth, and a high-speed turbine handpiece was loaded with a diamond turning needle with a standard particle size (105-125μm) to remove the axial enamel under water spray cooling, and the crown was made into a rectangle. The X-rayable infiltration resin and ICON prepared in Example 1 were applied to the cut surface according to the method of use described above, and two test pieces were grouped together to bond the cut surfaces. A universal testing machine was used for tensile testing, and the loading speed was 0.5mm·min -1 , until the specimen bonding interface breaks. The bonding strength is calculated as follows: tensile bonding strength (MPa) = tensile pressure (N) ÷ bonding area (mm 2 The control group was the ICON group. Figure 7 As shown, the bond strengths of the radiographically visible infiltrant resin and ICON were similar.

[0046] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields.

[0047] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An X-ray-developable infiltrative resin, characterized in that: It is a network polymer formed by the polymerization of resin matrix and developer through a cross-linking agent; The developer is an iodinated chemical substance containing an unsaturated bond.

2. The X-ray-discoverable infiltrative resin according to claim 1, characterized in that: The developer is one of (E)-3-iodoacrylate methyl, (E)-3-iodoacrylate ethyl, 3-iodo-2-propynyl N-butylcarbamate, iodo-2-ethyl acrylate, and 3-iodo-2-ethyl acrylate.

3. The X-ray-developable infiltrative resin according to claim 1, characterized in that: The resin matrix is ​​one of bisphenol A-glycidyl methacrylate, bisphenol-S-bis(3-methacryloyloxy-2-hydroxypropyl) ether, ethyl carbamate dimethacrylate, and isosorbide core-linked glycidyl methacrylate.

4. The X-ray-discoverable infiltrative resin according to claim 1, characterized in that: The crosslinking agent is one of triethylene glycol dimethacrylate and tricyclododecane dimethanol diacrylate.

5. The method for preparing an X-ray-developable infiltration resin according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Evenly mix the resin matrix, the crosslinking agent, the photoinitiator and the accelerator under light-proof conditions to obtain a permeation resin prepolymer; Step 2, adding a developer to the infiltration resin prepolymer obtained in step 1, and continuing to mix evenly under light-proof conditions to obtain a developed infiltration resin prepolymer; Step 3: When in use, the developable penetrating resin prepolymer obtained in step 2 is cured by light, and polymerized to obtain the X-ray developable penetrating resin.

6. The method for preparing an X-ray-developable infiltration resin according to claim 5, characterized in that: In step 1, the photoinitiator is one of camphorquinone, 1-phenyl-1,2-propanedione, benzophenone, 2-isopropylthioxanthone, and trimethylbenzoyl-diphenylphosphine oxide; 7. The method for preparing an X-ray-developable infiltration resin according to claim 5, characterized in that: In step 1, the accelerator is ethyl 4-dimethylaminobenzoate.

8. The method for preparing an X-ray-developable infiltrative resin according to claim 5, characterized in that: In step 1, the mass ratio of the resin matrix, the crosslinking agent, the photoinitiator and the accelerator is 27-50:31-70:0.5-1.5:0.5-3.

45.

9. The method for preparing an X-ray-developable infiltration resin according to claim 5, characterized in that: In step 2, the mass ratio of the developer to the infiltration resin prepolymer is 0.1 to 0.5:

1.

10. Use of the X-ray-displayable infiltration resin according to any one of claims 1 to 4 in the preparation of materials for diagnosing and treating cracked teeth.

Citation Information

Patent Citations

  • Tooth repair resin with X-ray radiation resistance and preparation method thereof

    CN103610599A

  • Low-shrinkage dental composite resin and preparation method thereof

    CN111557855A

  • Compound, polymer, composition, composition for film-forming, pattern-forming method, method for forming insulating film, method for producing compound, and method for producing idovinyl-containing polymer and acetylated

    CN114245792A